Role of interleukin-4 in regulation of age-related inflammatory changes in the hippocampus. - LYNCH, MARINA ANNETTA; MILLS, KINGSTON (The American Society for Biochemistry and Molecular Biology, 2005)
It is well documented that long term potentiation (LTP) is impaired in the hippocampus of the aged animal. Among the changes that contribute to this impairment is an increase in hippocampal concentration of the pro-inflammatory cytokine interleukin-1? (IL-1?), and increased IL-1?-induced signaling. In this study we investigated the possibility that these changes were a consequence of decreased concentration of the anti-inflammatory cytokine, IL-4, and decreased IL-4-stimulated signaling. We report that functional IL-4 receptors are expressed on granule cells of the dentate gyrus and that receptor activation results in phosphorylation of JAK1 and STAT6. Hippocampal IL-4 concentration was decreased with age, and this was accompanied by a decrease in phosphorylation of JAK1 and STAT6. The evidence indicates that IL-4 modulates expression of IL-1? mRNA and protein and that it attenuates IL-1?-induced impairment of LTP and phosphorylation of JNK and c-Jun. We argued that, if a decrease in hippocampal IL-4 concentration significantly contributed to the age-related impairment in LTP, then restoration of IL-4 should restore LTP. To test this, we treated rats with VP015 (phospholipid microparticles-incorporating phosphatidylserine), which increases IL-4 concentration in hippocampus. The data indicate that the VP015-induced increase in IL-4 concentration in hippocampus of aged rats and lipopolysaccharide (LPS)-treated rats was accompanied by a reversal of the age-related and LPS-induced impairment in LTP in perforant path granule cell synapses. We propose that interplay between pro-inflammatory and anti-inflammatory responses impact significantly on synaptic function in the hippocampus of the aged rat.
PUBLISHED
Keywords: Physiology